1962
DOI: 10.1111/j.1365-2621.1962.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene Hydrocarbon Composition of Citrus Oilsa

Abstract: SUMMARYA method for estimating the total monoterpene hydrocarbon content of citrus oils is described. The procedure consists of adding an internal standard (n‐butylbenzene) to the oils, spotting the mixture on a chromatostrip, eluting the hydrocarbons, and analyzing the eluate by gas chromatography. The total monoterpene hydrocarbon content is calculated from the weights of n‐butyl‐benzene and citrus oil used and from the areas under the peaks of the monoterpene hydrocarbons and n‐butylbenzene on the chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1965
1965
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Florida lime peel oil. The terpenes have been previously characterized by Ikeda et al (1962), and were confirmed in the present work. Tetradecane and pentadecane were identified as described above for lemon peel oil.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Florida lime peel oil. The terpenes have been previously characterized by Ikeda et al (1962), and were confirmed in the present work. Tetradecane and pentadecane were identified as described above for lemon peel oil.…”
Section: Resultssupporting
confidence: 66%
“…This curve was obtained on Florida cold-pressed Avon lemon oil. The terpenes have been previously identified by Stanley (1961) Ikeda (1962). Tetradecane and pentadecane were identified by correlating their mass spectral cracking patterns with those published by the American Petroleum Institute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…White bread, 67.6 g Hexanal, 1.35 mg 4890 (8292) Stofberg and Grundschober (1987), Lorenz and Maga (1972) 0.0004 Black pepper, 446 mg *α-Pinene, 1.02 mg 3700 Stofberg and Grundschober (1987), Pino et al (1990) Ikeda et al (1962), Wilson (1982a, 1982b) 0.0003 Lemon oil, 8 mg *Geranial, 90.4 µg 500 Stofberg and Grundschober (1987), Bernhard (1960), Wilson (1982a, 1982b) 0.0003 Lemon oil, 8 mg *β-Pinene, 832 µg 4700 Stofberg and Grundschober (1987), Ikeda et al (1962), Wilson (1982a, 1982b) 0.0002 Broccoli (raw), 6.71 g *p-Coumaric acid, 90.6 µg 657P ERS (1994), Schmidtlein and Herrmann (1975b) Stofberg and Grundschober (1987), Williams et al (1972), Buttery et al (1994) 0.0001 Onions, green, cooked, 137 mg *Oxalic acid, 31.5 µg 382 EPA (1996b), Kohman (1939), Vernot et al (1977) 0.0001 Coffee, 500 ml Hexanoic acid, 245 µg 3000 (5000) Stofberg and Grundschober (1987), Kung et al (1967) Ikeda et al (1962), Wilson (1982a, 1982b) Pino et al (1990) 0.00002 Grapefruit juice, 3.29 ml Methyl alcohol, 95.4 µg 5628 (7300) Stofberg and Grundschober (1987), Kirchner et al (1953), Lund et al (1981), Tanner and Limacher (1984), Pino et al (1986) 0.00002 Lemon oil, 8 mg *α-Terpinene, 23.2 µg 1680 Stofberg and Grundschober (1987), Wilson (1982a, 1982b) 0.00001 Lemon oil, 8 mg *α-Terpineol, 29.6 µg 2830 Stofberg and Grundschober (1987), Wilson (1982a, 1982b) (continues) tion, and manufacturing procedures and additionally require evidence of efficacy and safety, dietary supplements are not. We found that several dietary supplements would rank high in the HERT table if we had included them by using the recommended d...…”
Section: Ranking Possible Toxic Hazards From Naturally Occurring Chemmentioning
confidence: 99%